If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3p + -4) = 35 Reorder the terms: (-4 + 3p) = 35 Remove parenthesis around (-4 + 3p) -4 + 3p = 35 Solving -4 + 3p = 35 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3p = 35 + 4 Combine like terms: -4 + 4 = 0 0 + 3p = 35 + 4 3p = 35 + 4 Combine like terms: 35 + 4 = 39 3p = 39 Divide each side by '3'. p = 13 Simplifying p = 13
| 2(x-5)+3(2x-8)= | | 16=8 | | 6x+24=4.7 | | 9x^2-5x= | | 16=0.5r | | x*3-6=x*12-177 | | 27y^7+24y^4=0 | | x^2-x=462 | | 4x^2-6x-10=00 | | 3c+9=6(1c+9) | | 2x+37=4x-9 | | n=-120 | | 0.66+2y=4y-0.13 | | -6x-10=2+14 | | 5(12+4)=8x | | 490=-7n | | x^2+34x+11=0 | | 3x+24=38 | | 42=14n | | X+4y=1 | | 157-2x=34x+23 | | -21.536=1.6(9-m) | | x+x+1+x+4=-18 | | x*.5+2=0.33 | | 18x=180 | | x^3-2x^2-47x-6=0 | | 17-x=28-2x | | -0.1667(x-18)+0.5(x+2)=x-20 | | 4x^2+70x-304=0 | | 5x^2+7x+5x=0 | | 5x-15=8x-36 | | 25xy^2-36x=0 |